2013
DOI: 10.1159/000353257
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influence of COMT and BDNF Gene Polymorphisms on Resilience in Healthy College Students

Abstract: Purpose: Resilience refers to the individual positive capacity to cope with stress and to restore homeostasis, which may be mediated by adaptive neurobiological changes in the brain. We investigated the genetic influence of the catechol-O-methyltransferase (COMT) Val158Met and the brain-derived neurotrophic factor (BDNF) Val66Met for individual differences in resilience in healthy Korean college students. Methods: A sample of 321 healthy college volunteers (167 males, 154 females) was assessed by genotyping an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 47 publications
1
33
1
2
Order By: Relevance
“…COMT Val158Met polymorphism ( rs4680 ) was genotyped utilizing the TaqMan ® SNP Genotyping Assay as described by the manufacturer (Applied Biosystems, Carlsbad, CA, Assay ID# C_25746809_50). For the purpose of evaluating a potential protective benefit of the Met 158 allele, Met 158 / Met 158 and Met 158 / Val 158 were combined as a single group as previously described for COMT [3740] and other genetic polymorphisms in TBI [4143]. Therefore, for data reporting and all figures, this group is referred to as Met 158 .…”
Section: Methodsmentioning
confidence: 99%
“…COMT Val158Met polymorphism ( rs4680 ) was genotyped utilizing the TaqMan ® SNP Genotyping Assay as described by the manufacturer (Applied Biosystems, Carlsbad, CA, Assay ID# C_25746809_50). For the purpose of evaluating a potential protective benefit of the Met 158 allele, Met 158 / Met 158 and Met 158 / Val 158 were combined as a single group as previously described for COMT [3740] and other genetic polymorphisms in TBI [4143]. Therefore, for data reporting and all figures, this group is referred to as Met 158 .…”
Section: Methodsmentioning
confidence: 99%
“…Val 158 allele carriers display more resilience in their temperament (Kang et al, 2013), whereas Met 158 carriers have a higher risk of emotional dysregulation (Kempton et al, 2009). The link between COMT and novelty seeking was shown by Chen and colleagues, who demonstrated that males ( n = 250) carrying the Val/Val genotype displayed lower novelty seeking (Chen et al, 2011).…”
Section: Molecular Connection Between Novelty Seeking and Addictionmentioning
confidence: 99%
“…It should be mentioned that due to genetic pleiotropy, both COMT and BDNF have been found to be associated with several other aspects of cognition beyond WM, including reaction time (Das et al, 2014), cognitive flexibility (Kang et al, 2013), aging-related cognitive degradation (Ghisletta et al, 2014; Voelcker-Rehage et al, 2015), executive function (Leckie et al, 2014; Sapkota et al, 2015), and neurocognitive deficits in people with schizophrenia (Ahmed et al, 2015) or Parkinson's disease (Khalil et al, 2016). Nevertheless, WM has been the main focus of the previous literature in this field.…”
Section: Introductionmentioning
confidence: 99%